Nonalcoholic Fatty Liver Disease and Cardiovascular Disease: Overlapping Mechanisms - Møller, Søren; Kimer, Nina; Kronborg, Thit; Grandt, Josephine; Hove, Jens Dahlgaard; Barløse, Mads; Gluud, Lise Lotte (Seminars in Liver Disease, 2021)
Nonalcoholic fatty liver disease (NAFLD) denotes a condition with excess fat in the liver. The prevalence of NAFLD is increasing, averaging > 25% of the Western population. In 25% of the patients, NAFLD progresses to its more severe form: nonalcoholic steatohepatitis and >25% of these progress to cirrhosis following activation of inflammatory and fibrotic processes. NAFLD is associated with obesity, type 2 diabetes, and the metabolic syndrome and represents a considerable and increasing health burden. In the near future, NAFLD cirrhosis is expected to be the most common cause for liver transplantation. NAFLD patients have an increased risk of developing cardiovascular disease as well as liver-related morbidity. In addition, hepatic steatosis itself appears to represent an independent cardiovascular risk factor. In the present review, we provide an overview of the overlapping mechanisms and prevalence of NAFLD and cardiovascular disease.
Keywords: chronic liver diseases; nonalcoholic steatohepatitis; cirrhosis; atherosclerosis; coronary artery disease; diabetes; obesity